Pengaruh Persepsi Nasabah Terhadap Kesadaran Merek dan Implikasinya Pada Keputusan Pembiayaan - Sarwoto Sarwoto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The study was conducted on 150 respondents as MSME customers of PT Bank Syariah Indonesia, Branch Perbaungan, Serdang Bedagai District, North Sumatra. Respondents are customers having microfinance with current collectibility. Sampling was taken with accidental sampling method. Research model used SEM, and data processing used PLS 3.0 smart software. The results of the study answered the research objectives; perception influences financing decisions, brand awareness affects financing decisions, and brand awareness does not become a mediating variable in influencing perceptions of financial decisions.